Digital Transformation as a Supporter of Academic and Organizational Balance in Improving Student Achievement - maulida utami, kayla; marsofiyati; dewi utari, eka (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
Abstract. The results of the study are expected to provide a comprehensive picture of the impact of organizational involvement on academic achievement and offer practical recommendations in developing programs to support organizational-academic balance in higher education. his study aims to analyze the relationship between the balance of organizational and academic activities on student achievement, and to formulate strategies to improve academic achievement through the management of both aspects. The research method used is a qualitative method. This study uses a qualitative approach to gain an in-depth understanding of how students balance organizational and academic activities, and its impact on their academic achievement. This approach was chosen because it is able to explore the experiences, motivations, and strategies used by students in facing the challenges of this balan Keywords: Organization, Academic Achievement, Motivation To Learn